2018
DOI: 10.3390/metabo8030049
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolomics Analysis of Eggplant (Solanum melongena L.) Fruit and Its Correlation to Fruit Morphologies

Abstract: Eggplant is one of the most widely cultivated vegetables in the world and has high biodiversity in terms of fruit shape, size, and color. Therefore, fruit morphology and nutrient content become important considerations for both consumers and breeders who develop new eggplant-based products. To gain insight on the diversity of eggplant metabolites, twenty-one eggplant accessions were analyzed by untargeted metabolomics using GC-MS and LC-MS. The dataset of eggplant fruit morphologies, and metabolites specific t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 41 publications
2
18
1
Order By: Relevance
“…Other authors have also studied the fatty acids profile of eggplant fruit samples. In a study conducted by Hanifah et al [53], eggplant fruits of 21 different morphological varieties (color and shape) were evaluated and the results revealed the presence of some fatty acid molecules similar to the present work but the composition was mostly different. This can be justified by the different varieties of the fruit assessed and the application of another extraction method.…”
Section: Content Of Sugars Organic Acids and Fatty Acidssupporting
confidence: 78%
“…Other authors have also studied the fatty acids profile of eggplant fruit samples. In a study conducted by Hanifah et al [53], eggplant fruits of 21 different morphological varieties (color and shape) were evaluated and the results revealed the presence of some fatty acid molecules similar to the present work but the composition was mostly different. This can be justified by the different varieties of the fruit assessed and the application of another extraction method.…”
Section: Content Of Sugars Organic Acids and Fatty Acidssupporting
confidence: 78%
“…Furthermore, MS-based imaging (MSI) techniques such as laser ablated electrospray ionisation (Laser Ablation Electrospray Ionization LAESI; [148,149] and Matrix assisted laser desorption/ionization -imaging MS (MALDI-IMS) [150], can provide additional useful information on the localization of metabolites in planta. Untargeted metabolomics approaches have already successfully been applied to investigate the metabolome of for instance eggplant fruits [151], tomato fruit [152], potato tubers [153] and coffee leaves [154], providing useful information for breeders and manufacturers. A combination of robust metabolomics technologies for analysing primary and both volatile and non-volatile secondary metabolites in asparagus will contribute in expanding and improving our knowledge of the crop.…”
Section: The Potential Of Asparagus Metabolomicsmentioning
confidence: 99%
“…Other studies also have reported alkaloids, terpenes, and flavonoids in Solanum melongena L., but they focused on the plant’s fruit [ 38 , 46 , 47 ]. For example, Hanifah et al [ 48 ] conducted a study using an untargeted metabolomics analysis in eggplant fruit of 21 accessions, where they detected 136 and 207 peaks by LC-MS and GC-MS, respectively. Similar to our research, they identified alkaloids, terpenes, terpenoids, fatty acids, and flavonoids.…”
Section: Resultsmentioning
confidence: 99%